An ultra-thin, dual band, Sub 6 GHz, 5G and WLAN antenna for next generation laptop computers. Issue 4 (16th April 2020) - Kulkarni, Jayshri Sharad
Abstract : Purpose: The purpose of this manuscript is to present a novel, compact and ultra-thin "3"-shaped monopole antenna for wireless operations in the laptop computer. The thickness of the antenna is only 0.2 mm and is designed using only a pure copper strip of size 17.5 × 6 mm 2 . Design/methodology/approach: The simple structure of the proposed antenna consists of two monopole radiating strips, namely, AC and CD and an open-ended rectangular tuning stub BE of length 9mm. Findings: This structure inspires two resonating modes at 3.45 and 5.5 GHz and achieves the measured impedance band width as 20% (3.21-3.91) GHz in lower band (F_l) and 15% (5.05-5.85) GHz in the upper band (F_u) for voltage standing wave ratio < 2. These two bands cover 5GHz wireless local area network (WLAN) and 3.3-3.6GHz (sub 6GHz) 5G bands. The measured radiation performance including, nearly omnidirectional radiation patterns, a stable gain of around 5 dBi and excellent efficiency around 90% in both operating bands have been achieved. Furthermore, a simplified equivalent circuit model has been derived and its simulation is performed. The simulated and measured results are in good agreement, which demonstrates the applicability of the antenna structure for WiMAX/WLAN operations in the prominent ultra-thin laptop computers. Originality/value: The proposed antenna is designed without using any reactive elements, vias or matching circuits for excitation of WLAN and 5G bands in the laptop computers. The design also does not require any additional ground for mounting the antenna. The proposed antenna has a very low profile, is ultra-thin, cost-effective, easy to manufacture and can be easily embedded inside next generation laptop computers.